Modeling policy mix to improve the competitiveness of Indonesian palm oil industry - Roland Y. H. Silitonga; Joko Siswanto; Tota Simatupang; Senator Nur Bahagia (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: The purpose of this research is to develop a model that will explain the impact of government policies to the competitiveness of palm oil industry. The model involves two commodities in this industry, namely crude palm oil (CPO) and refined palm oil (RPO), each has different added value. Design/methodology/approach: The model built will define the behavior of government in controlling palm oil industry, and their interactions with macro-environment, in order to improve the competitiveness of the industry. Therefore the first step was to map the main activities in this industry using value chain analysis. After that a conceptual model was built, where the output of the model is competitiveness of the industry based on market share. The third step was model formulation. The model is then utilized to simulate the policy mix given by government in improving the competitiveness of Palm Oil Industry. Research limitations/implications: The model was developed using only some policies which give direct impact to the competitiveness of the industry. For macro environment input, only price is considered in this model. Practical implications: The model can simulate the output of the industry for various government policies mix given to the industry. Originality/value: This research develops a model that can represent the structure and relationship between industry, government and macro environment, using value chain analysis and hierarchical multilevel system approach.
Keywords: 650; palm oil industry; competitiveness; hierarchical multilevel system; policy mix